In Vivo Experiments with Dental Pulp Stem Cells for Pulp-Dentin Complex Regeneration - Sunil Kim; Su-Jung Shin; Yunjung Song; Euiseong Kim (Mediators of Inflammation)
In recent years, many studies have examined the pulp-dentin complex regeneration with DPSCs. While it is important to perform research on cells, scaffolds, and growth factors, it is also critical to develop animal models for preclinical trials. The development of a reproducible animal model of transplantation is essential for obtaining precise and accurate data in vivo. The efficacy of pulp regeneration should be assessed qualitatively and quantitatively using animal models. This review article sought to introduce in vivo experiments that have evaluated the potential of dental pulp stem cells for pulp-dentin complex regeneration. According to a review of various researches about DPSCs, the majority of studies have used subcutaneous mouse and dog teeth for animal models. There is no way to know which animal model will reproduce the clinical environment. If an animal model is developed which is easier to use and is useful in more situations than the currently popular models, it will be a substantial aid to studies examining pulp-dentin complex regeneration.